2018
DOI: 10.3390/f9030152
|View full text |Cite
|
Sign up to set email alerts
|

Overstory Structure and Surface Cover Dynamics in the Decade Following the Hayman Fire, Colorado

Abstract: Abstract:The 2002 Hayman Fire burned with mixed-severity across a 400-ha dry conifer study site in Colorado, USA, where overstory tree and surface cover attributes had been recently measured on 20 0.1-ha permanent plots. We remeasured these plots repeatedly during the first post-fire decade to examine how the attributes changed through time and whether changes were influenced by fire severity. We found that most attributes were temporally dynamic and that fire severity shaped their dynamics. For example, low-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…Although fire severity classification reportedly described the variability in first-order fire effects at this site (see Cocke et al 2005a), secondary tree mortality was indistinguishable among the burned (low, moderate, high) severity classes from 2002 to 2016, and ranged from 38 to 42% for all species combined. In low-severity plots, secondary tree mortality ranged from 26 to 62%, which may be high compared with patterns of secondary mortality reported for low-severity wildfire areas in western US dry forests elsewhere (Keyser et al 2008;Fornwalt et al 2018). In addition, tree mortality on unburned plots from 2002 to 2016 was 26%, double the initial mortality (2000 to 2002) one year following the Leroux Fire (Fig.…”
Section: Severity Patternsmentioning
confidence: 66%
“…Although fire severity classification reportedly described the variability in first-order fire effects at this site (see Cocke et al 2005a), secondary tree mortality was indistinguishable among the burned (low, moderate, high) severity classes from 2002 to 2016, and ranged from 38 to 42% for all species combined. In low-severity plots, secondary tree mortality ranged from 26 to 62%, which may be high compared with patterns of secondary mortality reported for low-severity wildfire areas in western US dry forests elsewhere (Keyser et al 2008;Fornwalt et al 2018). In addition, tree mortality on unburned plots from 2002 to 2016 was 26%, double the initial mortality (2000 to 2002) one year following the Leroux Fire (Fig.…”
Section: Severity Patternsmentioning
confidence: 66%
“…Furthermore, differences in pre‐fire forest structure may have been related to differences in eventual fire severity and in pre‐fire plant community composition. In particular, plots that eventually burned at low severity had a tendency to have increased bare ground cover and reduced litter cover, tree density, basal area and canopy cover compared to plots that eventually burned at moderate or high severity, although these differences were rarely significant (Appendix ) and differences in weather also likely played a strong role in eventual fire severity (Fornwalt et al., ). However, notably, the considerable variation in the pre‐fire ratio of cool‐mesic to warm‐xeric taxa (Figure a) is well explained by variation in pre‐fire canopy cover, with higher canopy cover plots associated with significantly higher ratios of cool‐mesic to warm‐xeric taxa (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Supporting this inference, we showed that extinctions of cool‐mesic lineages were most pronounced in high‐severity burned areas (Figure ), which had complete canopy removal at the plot scale. Although our post‐fire timeframe of 10 years may limit our ability to infer longer‐term community dynamics, we believe that the changes we observed in canopy structure and understory diversity should persist for the near future due in large part to the slow growth rates of surviving and establishing trees (Fornwalt et al., ; Malone et al., ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Trees surviving within beetle‐infested pine stands grew faster (Romme et al, 1986) and nutrient uptake by residual, live trees limited NO 3 –N leaching in simulated beetle outbreaks in Wyoming pine forests (Parsons et al, 1994). In this study, there were 3000 to 4500 trees ha −1 (0–200 cm tall) on uncut hillslopes (Supplemental Table S1) and dense understory plant cover (Supplemental Table S2), similar to conditions seen in nearby beetle‐infested forests (Fornwalt et al, 2018; Rhoades et al, 2018). Greater light and soil resource availability beneath dead overstory trees stimulate understory plants (Hawkins et al, 2013; Pec et al, 2015) and regenerating trees (Pelz et al, 2018), and this compensatory growth and nutrient demand appears sufficient to limit N losses.…”
Section: Discussionmentioning
confidence: 59%